2016
DOI: 10.3389/fncom.2016.00087
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Oscillations with Non-sinusoidal Morphology Produce Spurious Phase-to-Amplitude Coupling and Directionality

Abstract: Neuronal oscillations support cognitive processing. Modern views suggest that neuronal oscillations do not only reflect coordinated activity in spatially distributed networks, but also that there is interaction between the oscillations at different frequencies. For example, invasive recordings in animals and humans have found that the amplitude of fast oscillations (>40 Hz) occur non-uniformly within the phase of slower oscillations, forming the so-called cross-frequency coupling (CFC). However, the CFC patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
143
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(149 citation statements)
references
References 72 publications
5
143
1
Order By: Relevance
“…Though a very weak but true coupling effect cannot be discarded, based on our analysis of sawtooth waves (Figure 4 and Figure 4—figure supplement 2), we believe these results can be explained by theta harmonics, which would remain phase-locked to the fundamental frequency under small time shifts. Sharp signal deflections have been previously recognized to generate artifactual phase-amplitude coupling (Kramer et al, 2008; Scheffer-Teixeira et al, 2013; Tort et al, 2013; Aru et al, 2015; Lozano-Soldevilla et al, 2016). Interestingly, Hyafil (2015) recently suggested that the non-sinusoidality of alpha waves could underlie the 1:2 phase-locking between alpha and beta observed in human EEG (Nikulin and Brismar, 2006; see also Palva et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Though a very weak but true coupling effect cannot be discarded, based on our analysis of sawtooth waves (Figure 4 and Figure 4—figure supplement 2), we believe these results can be explained by theta harmonics, which would remain phase-locked to the fundamental frequency under small time shifts. Sharp signal deflections have been previously recognized to generate artifactual phase-amplitude coupling (Kramer et al, 2008; Scheffer-Teixeira et al, 2013; Tort et al, 2013; Aru et al, 2015; Lozano-Soldevilla et al, 2016). Interestingly, Hyafil (2015) recently suggested that the non-sinusoidality of alpha waves could underlie the 1:2 phase-locking between alpha and beta observed in human EEG (Nikulin and Brismar, 2006; see also Palva et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Parkinson rigidity has been linked to elevated CFC between the basal ganglia and motor cortex [94]. However, it is currently unclear whether this effect might constitute an artifact of the non-sinusoidal characteristics of beta rhythms in PD [95]. Furthermore, another recent report demonstrated that low frequency tACS that was frequency- and phase-matched to the tremor frequency could reduce the shaking through phase cancellation [96].…”
Section: Oscillopathies and Network Disordersmentioning
confidence: 99%
“…Note that, due to frequency smoothing as a result of estimating the envelope for the fast frequencies, the harmonic contributions are often “bleeding” together in the PAC plot. Therefore, great care must be taken when interpreting measures of PAC, in particular in the frequency bands of the higher harmonics, additionally taking into account the effective frequency smoothing (Kramer et al, 2008; Aru et al, 2015; Cole et al, 2016; Jones, 2016; Lozano-Soldevilla et al, 2016). In particular, Cole et al (2016) and Sheremet et al (2016) provide concrete examples from respective intracranial human and hippocampal rat recordings in which nonsinusoidal oscillations contribute to estimates of PAC.…”
Section: The Problem: Spurious Identification Pac Couplingmentioning
confidence: 99%